Bond strength and morphological interface of self-etching adhesives to demineralized and remineralized enamel - Hossam Elzuhery; Ola Ibrahim Fahmy; Inas AbdElmoneum Elghandour; Mohamed Adel Ezzat; Ali I. Abdalla (Elsevier, 2013)
Background/purpose: In the oral environment, enamel is continually exposed to episodes of demineralization and remineralization through various masticatory activities. During restorative procedures, it is a challenge to bond to enamel that may be altered. The purpose of this study was to evaluate the effects of different remineralizing agents and acid-etching pretreatments on the bond strength of two self-etching adhesives to enamel. Materials and methods: Bovine incisors were mounted in auto-curing acrylic resin and the enamel was flattened. Adhesive tape was used to cover half of the labial surface and the other half was demineralized using lactic acid. Specimens were divided into four groups according to the remineralization regimen: the first group was immersed in distilled water (control); the second group was remineralized using natural saliva; the third group was remineralized using fluoride containing Fluocal mouthwash; and the fourth group was remineralized using Tooth Mousse, a casein-containing remineralizing agent,. In half of the groups, the enamel was etched using phosphoric acid, and in the other half, the enamel was not etched. The G bond or Adper Prompt L Pop self-etching bonding agent was used to bond the composite to the enamel. The shear bond strength of specimens was tested, and the tooth restoration interface was examined using scanning electron microscopy. Results: The bond strength to enamel remineralized using Fluocal mouthwash or Tooth Mousse was higher than the normal and natural saliva-remineralized enamel. Etching improved the bond strengths of self-etching bonding agents especially if the enamel was remineralized. There was no statistically significant difference between the bond strengths of the two bonding agents. Conclusion: The use of a remineralizing agent had a positive effect on the bonding of self-etching adhesive systems to enamel especially if preceded by etching.